PENGARUH PROFESIONALISME, OBJEKTIVITAS, PENGALAMAN KERJA, DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT YANG DI HASILKAN (Studi Auditor Pada Kantor Akuntan Publik Di Malang) - Fenua Mustika Kristanti; Noor Shodiq Askandar; Afifudin Afifudin (Universitas Islam Malang, 2021)
The purpose of this study was to determine the effect of professionalism, objectivity, work experience, and auditor independence on the resulting audit quality. This research was conducted at a public accounting firm in Malang. This research was conducted from December 2020 to April 2020. The population in this study were auditors who worked in public accounting firms in Malang. The data used in this study is primary data. The total respondents used in this study were 51 respondents. The analysis used in this research is multiple linear regression. The results of this study are simultaneously the variables of professionalism, objectivity, work experience, and independence simultaneously have a significant effect on the audit quality variable. And partially the professionalism variable partially has a significant and positive effect on audit quality. The objectivity variable partially has a significant and positive effect on audit quality. The work experience variable partially has a significant and positive effect on audit quality. The independence variable partially has a significant and positive effect on audit quality.Keywords: Professionalism, Objectivity, Work Experience, Auditor Independence Quality Audit